2021
DOI: 10.3390/f12111503
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Family Labor in Agroforestry Systems in the Context of Global Transformations: The Case of the Inga and Camëntsá Communities in Putumayo, Colombia

Abstract: The Camëntsá and Inga indigenous communities still rely on agroforestry systems for their livelihood attainment, although globalization effects have also reached their settlements. Agroforestry systems, especially home gardens, are experiencing reduced size and species diversity and therefore gradually disappearing. This research aims to determine the indigenous family labor contribution to agroforestry systems as a strategy to secure their livelihoods. The methods include a census, household survey, interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…These are also species of high commercial value, while the Inga spp. provide food and incorporate nitrogen into the soil [53][54][55]; evidencing that the most common tree species found throughout the altitudinal gradient are of interest to provide shade, food and commercial timber similar to the findings of [56], and they are part of the native tree diversity, this could be due to the fact that the producers in the study area still have between 17% and 40% of remaining forests in the surroundings of the pastures [21].…”
Section: Dominant Tree Speciesmentioning
confidence: 54%
“…These are also species of high commercial value, while the Inga spp. provide food and incorporate nitrogen into the soil [53][54][55]; evidencing that the most common tree species found throughout the altitudinal gradient are of interest to provide shade, food and commercial timber similar to the findings of [56], and they are part of the native tree diversity, this could be due to the fact that the producers in the study area still have between 17% and 40% of remaining forests in the surroundings of the pastures [21].…”
Section: Dominant Tree Speciesmentioning
confidence: 54%
“…Motiur et al [140] found that agroforestry practices contributed 15.9 and 11.8 percent of household income in southwest and northern Bangladesh, respectively. As a result, according to the number of workers, agroforestry practices continue to be the main source of income and food for rural communities in the study area [22,97,100,141]. However, the insignifcance of agroforestry practices in terms of income generation can be attributed to a variety of factors.…”
Section: Efects Of Agroforestry Practices On Household Farmmentioning
confidence: 99%
“…There are also 20 percent of farmers with just 2 family members, typically young, newly married farmers. Families with multiple members may include extended family or multiple family heads, often engaging in coffee farming to reduce labor costs, enhance local food security, and generate extra income [16]. The composition of a farmer's household can significantly influence their economic activities.…”
Section: Figure 1 Characteristics Of Coffee Farmersmentioning
confidence: 99%